2022
DOI: 10.1007/s11071-022-07800-0
|View full text |Cite
|
Sign up to set email alerts
|

An efficient analytical approach to assess root cause of nonlinear electric vehicle gear whine

Abstract: Noise, vibration, and harshness (NVH) issues pose considerable challenges for electric vehicle powertrain engineers. Gear vibrations generate an intrusive gear whine noise, with significant impact on the sound quality of electric powertrains. Dynamic transmission error (DTE) is the most quantitative indicator for gear NVH. Backlash, time variable meshing stiffness and damping contribute to DTE. Hence, a better understanding of these excitation sources is essential. A gear tribodynamics model is developed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…This may have implications for interactions between pedestrians and electric vehicles. Electric vehicle noise output is much lower than that of internal combustion engines, with research being conducted to predict the intrusive noise of electric vehicles [35] in order to further reduce it. However, although previous research has found that distracted pedestrians are poorer at detecting approaching vehicle noise, their gap acceptance is unaffected [36].…”
Section: Discussionmentioning
confidence: 99%
“…This may have implications for interactions between pedestrians and electric vehicles. Electric vehicle noise output is much lower than that of internal combustion engines, with research being conducted to predict the intrusive noise of electric vehicles [35] in order to further reduce it. However, although previous research has found that distracted pedestrians are poorer at detecting approaching vehicle noise, their gap acceptance is unaffected [36].…”
Section: Discussionmentioning
confidence: 99%
“…To determine the key parameters related to the specific noise and vibration issues, linear analysis can be performed as a fundamental step to reveal the critical system parameters relevant to the NVH problems in question [1][2][3][4][5][6][7]. When it comes to examining system responses, the analytical approach is commonly more efficient for diagnosing and improving vehicle driveline problems under symmetric conditions than the experimental method, as experiments generally require more significant costs and time than simulations [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…To verify this measurement, the authors exploited it to compare the theoretical and experimental methods. Mughal et al introduced a gear tribodynamics model using the potential energy method to estimate time variable meshing stiffness (TVMS) [17]. In this research, the authors suggested a fully analytical and time-efficient model for lubricated contact stiffness based on transitions in the regimes of lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…Although the engine is no longer the primary source of noise for new energy vehicles, the sound pressure level in such vehicles is significantly lower than that of conventional vehicles. However, the acoustical comfort of new energy vehicles has not been significantly improved, and the acoustical quality problem is more outstanding [5][6][7]. The main cause is the alteration of sound quality parameters such as loudness, sharpness, and roughness brought on by structural resonance and abnormal noise.…”
Section: Introductionmentioning
confidence: 99%